Pulicaria vulgaris Gaertn. (Asteraceae) - A new species record for Bangladesh - Rahman, Md. Oliur; Sultana, Mahbuba; Begum, Momtaz; Hassan, Md. Abul (Bangladesh Journal of Plant Taxonomy, 2011)
Not available. Keywords: Pulicaria vulgaris; New record; Bangladesh; Asteraceae. DOI: http://dx.doi.org/10.3329/bjpt.v18i2.9308 Bangladesh J. Plant Taxon. 18(2): 205-208, 2011 (December)